2023
DOI: 10.3390/ijms241511978
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reprogramming in Obsessive–Compulsive Disorders: A Review of Gut–Brain Communication and Emerging Evidence

Abstract: Obsessive–compulsive disorder (OCD) is a debilitating mental health disorder characterized by intrusive thoughts (obsessions) and repetitive behaviors (compulsions). Dysbiosis, an imbalance in the gut microbial composition, has been associated with various health conditions, including mental health disorders, autism, and inflammatory diseases. While the exact mechanisms underlying OCD remain unclear, this review presents a growing body of evidence suggesting a potential link between dysbiosis and the multiface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 282 publications
0
1
0
Order By: Relevance
“…Recent studies have revealed close associations between human commensal microbes and complex diseases such as mental disorders, cardiovascular diseases, and cancer ( Xiao et al, 2022 ; Bendriss et al, 2023 ; Chen et al, 2023 ). Modulating the gut microbiota and enhancing gut barrier function has emerged as a promising new approach for preventing and treating certain diseases ( Koning et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed close associations between human commensal microbes and complex diseases such as mental disorders, cardiovascular diseases, and cancer ( Xiao et al, 2022 ; Bendriss et al, 2023 ; Chen et al, 2023 ). Modulating the gut microbiota and enhancing gut barrier function has emerged as a promising new approach for preventing and treating certain diseases ( Koning et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%